Wages, Rents, and the Quality of Life - Roback, Jennifer (Journal of Political Economy, 1982)
This study focuses on the role of wages and rents in allocating workers to locations with various quantities of amenities. The theory demonstrates that if the amenity is also productive, then the sign of the wage gradient is unclear while the rent gradient is positive. The theory is extended to include the housing market and nontraded goods. These extensions require little modification of the conclusion. The empirical work on wages shows that the regional wage differences can be explained largely by these local attributes. With the use of site price data, implicit prices are estimated and quality of life rankings for the cities are computed.